The influence of density on frequency-dependent selection by wild birds feeding on artificial prey - Allen, J. A. (1998)
Previous work has demonstrated frequency-dependent selection by wild garden birds when feeding on green and brown pastry 'baits'. When the density of baits is low, the common colour is eaten disproportionately more than the rare colour (apostatic selection), and when the density is very high, the rare colour is eaten disproportionately more than the common (anti-apostatic selection). We explored the relationship between frequency-dependent predation and density in an experiment at 16 separate sites, using four levels of density and two frequencies of green and brown. Analysis of estimates of log-relative risk ratios showed little evidence for frequency-independent selection, but frequency-dependent selection changed gradually from apostatic at low density to anti-apostatic at high density. The validity of these conclusions in terms of individual bird behaviour was confirmed by Monte-Carlo simulations. We thus conclude that selection by wild birds feeding on green and brown artificial prey is frequency dependent, and that the strength and direction of this selection changes with prey density in a gradual and predictable manner.